2023
DOI: 10.1002/jsfa.12488
|View full text |Cite
|
Sign up to set email alerts
|

Effect of mussel polysaccharide on glucolipid metabolism and intestinal flora in type 2 diabetic mice

Abstract: BACKGROUND Type 2 diabetes (T2D) mellitus is a major metabolic disease, and its incidence and lethality have increased significantly in recent years, making it a serious threat to human health. Among numerous previous studies, polysaccharides have been shown to alleviate the adverse effects of T2D, but there are still problems such as insufficient analysis and poor understanding of the mechanisms by which polysaccharides, especially those of marine origin, regulate T2D. METHODS In this study, we used multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(2 citation statements)
references
References 52 publications
0
2
0
Order By: Relevance
“…Ginger polysaccharides are important components in ginger, with various biological activities, such as antioxidant activity [84], immune regulation [85], antitumor activity [86], anticoagulant activity [87], and hypoglycemic activity [88]. Wang et al [89] found that ginger polysaccharide effectively reduced the blood sugar level of diabetic mice, increased the abundances of the beneficial bacteria Oscillospira, Adlercreutzia, Akkermansia, and Lactobacillus, and reduced the abundance of the harmful bacteria Prevotella. Among them, the genus Oscillospira is associated with obesity; Adlercreutzia is a bacterium that can produce SCFAs and has anti-inflammatory effects [90].…”
Section: Gingermentioning
confidence: 99%
“…Ginger polysaccharides are important components in ginger, with various biological activities, such as antioxidant activity [84], immune regulation [85], antitumor activity [86], anticoagulant activity [87], and hypoglycemic activity [88]. Wang et al [89] found that ginger polysaccharide effectively reduced the blood sugar level of diabetic mice, increased the abundances of the beneficial bacteria Oscillospira, Adlercreutzia, Akkermansia, and Lactobacillus, and reduced the abundance of the harmful bacteria Prevotella. Among them, the genus Oscillospira is associated with obesity; Adlercreutzia is a bacterium that can produce SCFAs and has anti-inflammatory effects [90].…”
Section: Gingermentioning
confidence: 99%
“…However, these medications cause significant side effects (Grant et al, 2011). Numerous studies have elucidated the safeguarding influence of polysaccharides in individuals diagnosed with type 2 diabetes (Luo et al, 2022; Mo et al, 2019; Oyenihi et al, 2017; Wang et al, 2023). An increasing volume of research suggests that alterations in the gut microbiota significantly correlate with T2DM (Forslund et al, 2015; Zhang et al, 2015).…”
Section: Introductionmentioning
confidence: 99%